ANÁLISE DA MARGEM DE CONTRIBUIÇÃO DE UM HECTARE DE TRIGO EM PROPRIEDADE RURAL DA AGRICULTURA FAMILIAR - Andres, Vanessa; Schneider, Aline M.; Gaelzer, Graziela; Zingler, Cristiane L. (Salão do Conhecimento, 2013)
Resumo